The Efficacy of Single-Application NPWTi-d for the Salvage of Infected Breast Prostheses: A Multi-Center Study - Jason C. Llaneras, MD; Robert Craig Clark, MD; Lauren Antognoli, MD; Emily Finkelstein, MD; Luci Hulsman, BS; Luther Holton, MD; Devinder Singh, MD; R. Jason VonderHaar, MD; Risal Djohan, MD; Aladdin H. Hassanein, MD; Chris M. Reid, MD (Plastic and Reconstructive Surgery, Global Open)
Background:. Breast prosthesis infections are challenging and traditionally managed with prosthesis removal and delayed reconstruction. Single-application negative pressure wound therapy with instillation and dwell (NPWTi-d) has shown promise for salvaging infected implants, though prior studies have been small and heterogeneous. This study analyzes outcomes and compares protocols from four institutions. Methods:. Data were collected on 56 patients (59 breasts) who underwent NPWTi-d salvage for peri-prosthetic infections. Patients with fewer than 3 months of follow-up were excluded. Salvage protocols included explantation, NPWTi-d application, antibiotics, and replantation. Successful salvage was defined as prosthesis retention without further explantation for at least 90 days posttreatment. Results:. Intervention occurred on average 66 days after the index procedure. Methicillin-resistant organisms were cultured in 15% of cases. NPWTi-d was applied for an average of 61 hours with dwell times of 18 minutes every 3 hours, using institution-specific instillates. All patients were discharged with new prostheses (65% expanders, 35% implants) after an average hospital stay of 4 days. At 90-day follow-up, 71% of patients had no further complications, and 85% were successfully salvaged. Conclusions:. This is the largest study to evaluate NPWTi-d for salvaging infected breast prostheses. The high success rate highlights the method’s efficacy, safety, and potential for preserving reconstruction. These straightforward protocols can significantly improve patient outcomes and reduce healthcare costs, offering a valuable option for managing prosthesis infections.